MiR-106a is an independent prognostic marker in patients with glioblastoma - Zhao, Shiguang (Oxford University Press, 2013)
BACKGROUND: Very little is known regarding correlation of micro RNA (miR)–106a with clinical outcomes of patients with glioblastoma multiforme (GBM). This study determined whether miR-106a could be used as an independent prognostic biomarker in those patients. METHODS: A total of 156 GBM patients were divided into 2 cohorts. In the first cohort, matched fresh frozen and formalin-fixed paraffin-embedded (FFPE) samples were collected from 24 GBM patients, while in the second cohort, only FFPE samples were collected from 132 GBM patients. MiR-106a expression levels were examined by quantitative real-time PCR in the 2 cohorts and further validated by in situ hybridization assay in the second cohort. The correlation between miR-106a expression levels and overall survival was evaluated in the second cohort of 114 GBM patients available for follow-up by a log-rank test and a multivariate Cox proportional hazards model. RESULTS: Our data showed a very good correlation of miR-106a or U6 expression between fresh frozen and FFPE GBM specimens, with Pearson's correlation coefficients of 0.849 and 0.823, respectively (P < .001). Their expression levels in archival FFPE samples were quite stable for at least 7 years when stored at room temperature. Multivariate analysis revealed that the expression level of miR-106a was an independent and significant predictor of overall survival in GBM patients (P = .011). CONCLUSIONS: MiR-106a expression was relatively abundant and stable in a large cohort of archival FFPE GBM specimens and could be used as an independent prognostic biomarker in those patients. Thus, miR-106a can be used to predict prognosis and treatment response in individual GBM patients.